Influence of simvastatin on bone regeneration of tibial defects and blood cholesterol level in rats - Anbinder, Ana Lia; Junqueira, Juliana Campos [UNESP]; Mancini, Maria Nadir G.; Balducci, Ivan [UNESP]; Rocha, Rosilene Fernandes da; Carvalho, Yasmin Rodarte (FapUNIFESP (SciELO), 2006)
The purpose of this study was to evaluate the effects of simvastatin, by oral or subcutaneous administration, on tibial defects regeneration and blood cholesterol level in rats. A surgical defect was made on the right tibia of 40 male animals assigned to 4 groups (n=10), based on two routes of administration and on the use or not of simvastatin: subcutaneous injection of simvastatin (7 mg/kg) (group AT) or only the vehicle of drug suspension (group AC), above the defect area, for 5 days; and 20 mg/kg of simvastatin macerated on water (group BT) or only water (group BC), orally, daily, during the whole observation period. The animals were sacrificed after 15 or 30 days, when blood samples were analyzed to check plasma cholesterol levels. Tibiae were removed and, after decalcification and routine laboratorial processing, histological and histomorphometrical analyses were carried out. ANOVA was used for statistical analysis at 5% signficance level. The histological and histomorphometrical analyses showed significant differences only between the experimental periods (p<0.05). Animals sacrificed after 30 days showed better bone repair (p<0.05). There was no statistically significant difference (p>0.05) for blood cholesterol levels between the groups. In conclusion, simvastatin administration either orally or subcutaneously did not improve bone repair of experimental tibial defects and did not alter blood cholesterol levels in rats.
Keywords: Bone regeneration; Cholesterol; Rats; Simvastatin; cholesterol; chromogenic substrate; diagnostic agent; hypocholesterolemic agent; simvastatin; animal; blood; bone development; bone disease; bone regeneration; bone remodeling; drug effect; male; oral drug administration; osteoblast; osteocyte; pathology; periosteum; rat; subcutaneous drug administration; tibia; time; Wistar rat; Administration, Oral; Animals; Anticholesteremic Agents; Bone Diseases; Bone Regeneration; Bone Remodeling; Chromogenic Compounds; Injections, Subcutaneous; Male; Osteoblasts; Osteocytes; Osteogenesis; Periosteum; Rats, Wistar; Tibia; Time Factors